Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/5869257
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of Th1 Cytokines and the Clinical Significance of the IFN-γ/TNF-α Ratio in Acute Brucellosis

Abstract: Background T-helper type 1 (Th1) cells and Th1-produced cytokines play essential roles in the immune response to foreign pathogens, such as Brucella spp. The aim of this study was to evaluate the dynamic changes of Th1 cells and Th1-produced cytokines in patients with acute brucellosis and their impact on clinical decision-making. Methods Fifty-one individuals with acute brucellosis and 17 healthy subjects were enrolled in this study. The brucellosis patients were diagnosed based on clinical symptoms, laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“… 16 , 17 In particular, TNF-α, IFN-γ, IL-2, and IL-10 levels are affected during Brucella infection. 16 , 18 , 19 Additionally, the level of these cytokine indicates the status of the immune response and disease progression. However, the role of Th1/Th2/Th17 cytokines in acute brucellosis infection and treatment still remains partially defined or debated.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 In particular, TNF-α, IFN-γ, IL-2, and IL-10 levels are affected during Brucella infection. 16 , 18 , 19 Additionally, the level of these cytokine indicates the status of the immune response and disease progression. However, the role of Th1/Th2/Th17 cytokines in acute brucellosis infection and treatment still remains partially defined or debated.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the gold standard for diagnosing this disease is leukocyte culture, this test has a high false-negative rate. Moreover, its cost and a 10-day delay before confirmation restrict its use as a standard diagnostic test in acute Brucellosis (6). As a result, clinicians chiefly rely on other laboratory tests to evaluate patients with brucellosis, such as agglutination test, white blood cell (WBC) counts, platelet (PLT) counts, liver function tests, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, clinicians chiefly rely on other laboratory tests to evaluate patients with brucellosis, such as agglutination test, white blood cell (WBC) counts, platelet (PLT) counts, liver function tests, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). Nevertheless, the diagnosis of brucellosis remains a challenge in most cases (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of IFN-γ has important clinical significance in brucellosis. Xu [ 10 ] reported that the increased level of IFN-γ and TNF-α in the serum of patients with acute brucellosis. Freeman [ 11 ] found that CXCR3 was significantly increased in severe chronic non-obstructive diseases.…”
Section: Introductionmentioning
confidence: 99%